Differential impact of dual-active ingredient long-lasting insecticidal nets on primary malaria vectors: a secondary analysis of a 3-year, single-blind, cluster-randomised controlled trial in rural Tanzania. Issue 5 (May 2023) - Matowo, Nancy S; Kulkarni, Manisha A; Messenger, Louisa A; Jumanne, Mohamed; Martin, Jackline; Mallya, Elizabeth; Lukole, Eliud; Mosha, Jacklin F; Moshi, Oliva; Shirima, Boniface; Kaaya, Robert; Rowland, Mark; et al.
Summary: Background: Gains in malaria control are threatened by widespread pyrethroid resistance in malaria vectors across sub-Saharan Africa. New long-lasting insecticidal nets (LLINs) containing two active ingredients (dual active-ingredient LLINs) have been developed to interrupt transmission in areas of pyrethroid resistance. We aimed to evaluate the effectiveness of three dual active-ingredient LLINs compared with standard pyrethroid LLINs against pyrethroid-resistant malaria vectors in rural Tanzania. Methods: In this study, we did a secondary analysis of entomological data from a four-group, 3 year, single-blind, cluster-randomised controlled trial carried out between Feb 18, 2019, and Dec 6, 2021. We conducted quarterly indoor mosquito collections using the Centers for Disease Control and Prevention light trap, in eight houses in each of the 84 study clusters in the Misungwi district, northwestern Tanzania. Anopheles vectors were then tested for malaria parasites and identified at species level, to distinguish between sibling species of the Anopheles gambiae and Anopheles funestus groups, using molecular laboratory techniques. The primary outcomes were density of different malaria vector species measured as the number of female Anopheles collected per household per night, the entomological inoculation rate (EIR), an indicator of malaria transmission, and sporozoite rate. Entomological outcomes were assessed on the basis of intention to treat, and the effect of the three dual active-ingredient LLINs was compared with the standard pyrethroid LLINs at household level. Findings: Dual active-ingredient LLINs had the greatest effect on Anopheles funestus sl, the most efficient vector in the study area, with comparatively weak effect on An arabiensis . An funestus density was 3∙1 per house per night in the pyrethroid LLIN group, 1∙2 in the chlorfenapyr pyrethroid LLIN group (adjusted density ratio [aDR]=0∙26, 95% CI 0∙17–0∙14, p<0∙0001), 1∙4 in the piperonyl-butoxide pyrethroid LLIN group (aDR=0∙49, 0∙32–0∙76, p=0∙0012), and 3∙0 in the pyriproxyfen pyrethroid LLIN group (aDR=0∙72, 0∙47–1∙11, p=0∙15). Malaria transmission intensity was also significantly lower in the chlorfenapyr pyrethroid group, with 0∙01 versus 0∙06 infective bites per household per night in the pyrethroid LLIN group (aDR=0∙21, 0∙14–0∙33, p<0∙0001). Ecological niche models indicated that vector-species distribution was stable following LLIN intervention despite the reductions observed in An funestus sl density. Interpretation: Chlorfenapyr pyrethroid LLINs were the most effective intervention against the main malaria vector An funestus sl over 3 years of community use, whereas the effect of piperonyl-butoxide pyrethroid LLIN was sustained for 2 years. The other vector, An arabiensis, was not controlled by any of the dual active-ingredient LLINs. Additional vector control tools and strategies targeted to locally prevalent vector species evading dual active-ingredient LLINs should be deployed to further reduce malaria transmission and achieve elimination. Funding: The Department for International Development, UK Medical Research Council, Wellcome Trust, the Department of Health and Social Care, and The Bill & Melinda Gates Foundation via the Innovative Vector Control Consortium.